The Politics of Poverty: Higher Education and Low Income Adult Learners - Catherine A. Hansman (Adult Education Research Conference, 2006)
The purpose of this paper is to examine and discuss the growing trends in higher education in the United States that narrow educational opportunities for poor and working-class adult learners.
Keywords: Higher education; low-income adults; access to higher education